The Role of Islamic Religious Education Teachers in Instilling Character Values in Students at SMAN 1 Ngemplak - Wakhidah Kurniawati; Meti Fatimah (South Sulawesi Education Development (SSED), 2024)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in instilling character values ​​in students at SMAN 1 Ngemplak and to analyze the strategies implemented by PAI teachers in the process. Student character is an important focus in modern education, where PAI teachers have the responsibility to shape students' personalities with noble morals through the integration of Islamic values ​​in learning. Data were collected through in-depth interviews with PAI teachers, observation of the learning process, and documentation of religious activities involving students at SMAN 1 Ngemplak. Meanwhile, the analysis method used is descriptive qualitative, namely data collection, data presentation, and conclusion. The results of the study show that PAI teachers play a central role as role models, moral educators, and spiritual guides. They also use various strategies in instilling character values, such as the integration of values ​​in learning, habituation, and religious extracurricular activities. This study concludes that the role and strategies implemented by PAI teachers are very effective in shaping the character of students who are disciplined, honest, responsible, and have empathy for others. This study recommends increasing cooperation between teachers, parents, and the community to strengthen the instillation of character values ​​in the school environment and its surroundings.